Mathematical Reasoning Ability and Mathematics Self-efficacy in Gender Differences - Ratu Perwira Negara, Habibi; ., Wahyudin; Nurlaelah, Elah; ., Marzuki; Heniati Santosa, Farah; Bahri, Samsul (KnE Social Sciences, 2024)
Gender differences and aspects of self-efficacy are factors influencing the success of the mathematics learning process. This study aims to obtain an explanation of mathematical reasoning abilities based on gender differences in terms of mathematical self-efficacy. The sample of this research is a collection of scores of mathematical reasoning abilities, gender differences, and mathematical self-efficacy scores of XIth grade students from a high school in Bandung. The research sample consisted of 35 students, consisting of 19 male and 16 female students. The research instruments were tests of mathematical reasoning abilities (MRA), gender differences, and a mathematics self-efficacy (SEM) questionnaire. Data analysis was done using ANACOVA, with MRA in the form of interval scale, gender category scale, and SEM as covariate with interval scale. The results of the study were as follows: (1) there is a linear relationship between mathematical self-efficacy and mathematical reasoning ability; (2) there is no difference in students’ mathematical reasoning abilities based on gender differences. Furthermore, SEM students and gender differences have an influence on the MRA achieved by students. Keywords: gender differences, mathematical reasoning ability, mathematics self-efficacy